Appeal for new ambulance (press cutting)
041-0127-001 APPEAL FOR NEW AMBULANCE 2 Nov MESSAGE DESCRIBES BOMBING An appeal for a new ambulance for the Scottish unit in Spain, to replace that destroyed in Friday's bombing at Parla, near Madrid, was contained in a cablegram received by Sir D. M. Stevenson in Glasgow yesterday. The message from Miss Jacobsen, the only woman member of the unit, stated: — " Heavily bombarded on the Parla front. Watters, Girvan, Mahon and Jacobsen had miraculous escapes. " Watters inconsolable about complete loss of his ambulance. Hopes Glasgow citizens will present him with another. " Girvan's ambulance badly damaged by shrapnel, but being repaired." 292/946/41/127